Distribution of Hepatitis B Virus Genotypes and Its Association with Severity of Liver Disease in Patients with Chronic Hepatitis B in Uttar Pradesh, India - Kumar, Ajay (Springer-Verlag, 2011)
The present study was designed to investigate the distribution of genotypes and its association with severity of liver disease in patients with Chronic Hepatitis B (CHB) in Uttar Pradesh, India. One hundred five HBsAg positive patients were selected for the study. The DNA was extracted by using pure viral DNA extraction kit. The genotype of Hepatitis B virus (HBV) was identified by using polymerase chain reaction- based restriction fragment length polymorphism (PCR-RFLP) method, by using AvaII and DpnII restriction enzyme to see the different patterns of cleavage that would occur at this specific site. Among 105 HBsAg positive chronic liver disease patients 58 patients were positive for HBeAg and 47 samples were HBeAg negative. Genotyping was done successfully in 91 samples. Genotype A was identified in 22% and genotype D in 78% CHB patients. Genotype A showed elevated liver enzymes much more than genotype D. The Child Pugh classification of 20 patients with genotype A was class A (n = 2), B (n = 9), C (n = 9) and of genotype D was class A (n = 13), B (n = 50) and C (n = 8). In conclusion our results showed that Genotype D was the commonest genotype in Uttar Pradesh, whereas genotype A had significantly more elevated ALT/AST levels than genotype D. (P < 0.05). Child Pugh Grade B was significantly more in patients with genotype D, whereas Child Pugh Grade C was more in genotype A. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13337-011-0034-3) contains supplementary material, which is available to authorized users.